Synergistic Effect of Glycol Ethers with a Kinetic Inhibitor (Poly(VP-VCap)) for Sweet Natural Gas Hydrate Formation: (Concentration Effect of Glycol Ethers) - Ghasem Khatinzadeh; Sohrab Taghipoor; Ali Mehdizdaeh; Ahmad Roozbehani (Journal of Petroleum Science and Technology, 2019)
Formation of natural gas hydrate is a serious problem in the gas and oil industry because it can plug pipelines and destroy the equipment. This study aimes to evaluate the concentration effect of glycol ethers on their synergism with a commercial kinetic hydrate inhibitor (Luvicap 55W) in sweet natural gas-water systems at a constant temperature of 4 oC and pressure of 95 bar. Hydrate formation experiments have been designed and conducted in a static, stirred autoclave. Finally, the results indicated that concentration changes dosen’t affect the inhibition time greatly, while the growth rate of hydrate crystals decreases considerably with the increase in the concentration of glycol ethers.